Relationships between indicators of internal aggression and age categories of athletes. The problem of moral verbality in sports - Skrygin S. V.; Yurchenko A. L.; Galochkin P. V.; Anurov V. L. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the dominant aggressiveness of various age categories of athletes as an etymological factor of inappropriate behavior after the end of a sports career and a potential factor in their asocialization.